The Personality of Sugihara Chiune (1900–1986) and the Preservation of Historical Memory of Him After World War II - D. I. Vorobeva (Ежегодник Япония, 2023)
The article is dedicated to researching the biography and historical memory of the Japanese consul in Lithuania in 1939–1940 and the only Japanese Righteous Among the Nations Sugihara Chiune, who issued 2139 transit visas to Polish and Lithuanian Jews from July to September 1940, which helped them escape the tragedy of the Holocaust in Lithuania after the German attack on the USSR. For the reader’s convenience, the work is divided into 5 parts. The first focuses on the stages of Sugihara’s career before his appointment as consul in Kaunas: his early biography (1900–1919), his study of Russian in Harbin (1919–1924), his work at the Japanese Consulate General (1925–1932) and the Manchukuo Foreign Ministry (1932–1935), his transfer to the Japanese Foreign Ministry in Tokyo (1935–1937), and his departure for a diplomatic mission in Finland (1937–1939). Along with a description of his professional development, an important place in this part is occupied by an analysis of Sugihara’s personal life and the process of shaping his views, which subsequently determined his willingness to act in a way that, at first glance, was not typical of a diplomat of militarist Japan. The second and third parts describe Sugihara’s activities in Kaunas (1939– 1940). Attention is paid both to his intelligence activities with the support of Polish agents and to his private life, the events of which developed Sugihara’s earlier capacity for sympathy for people of other nationalities. It also details the process of issuing transit visas to Jewish refugees, deliberately carried out in violation of Foreign Ministry instructions, as well as estimates of the number who left Lithuania thanks to Sugihara and describes their further journey. The fourth part, although small, covers a broad period in the life of the former Japanese consul in Lithuania: his work in Prague (1940–1941), Königsberg (1941), and Bucharest (1941–1944), internment and repatriation to Japan (1944–1947), work in various commercial firms (1947–1975) and the process of recognition as a Righteous (1984). Finally, the final part of the paper is devoted to the analysis of the historical memory of Sugihara in Israel, Japan, the USA, Poland, Lithuania, and Russia, as well as identification of the main differences in its nature and the reasons that determined this heterogeneity.